Analisis Otonomi dan Pembiayaan Pendidikan dalam Meningkatkan Mutu Pendidikan - Mujahidah, Atika; Mayangsari, Alfira Okta; Kumairo, Mala Nur (Lembaga Yasin AlSys, 2024)
This article aims to investigate regional autonomy and education financing management in relation to efforts to improve the quality of education. The method used is the Systematic Literature Review (SLR) method, defined as a systematic literature review that is translated into Indonesian. This SLR method uses the PRISMA model. The results of this study show that education financing management affects the quality of school education. Financing management is a process of optimizing existing sources of funds, allocating available funds and distributing them as facilities or means of supporting the learning process so as to create an effective and efficient and much better learning process. To achieve good school quality, education costs must be managed optimally and maximally. Therefore, the stages of education financing management need to be considered and prioritized.